Tomografia por Biosusceptometria de Corrente Alternada (tBAC): desenvolvimento, caracterização, implementação - Matos, Ronaldo Vitor Reis [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The Biosusceptometry AC (BAC) is a research tool that has been extensively explored by the group Biomagnetism IBB-UNESP for monitoring of the gastrointestinal tract, its response to a known drug or in vivo performance of solid dosage forms. During this period the BAC, which has the characteristics of high sensitivity and low cost, has been developed primarily for recording signals contraction of activity and traffic human gastrointestinal tract. With the possibility of producing images with this instrumentation, it was possible to evaluate different situations in vitro and in vivo for physiological studies and pharmaceuticals. Considering the good performance of this system to produce planar images, the first aim of the BAC system tomography (TBAC) was to evaluate the system performance of BAC to produce tomographic images of phantoms ferromagnetic for a single channel system. All these applications were only possible because of their sensitivity to materials of high magnetic suscepitibility as ferrite, which allow to produce an electrical signal proportional to the variation of the magnetic flux generated by the presence of magnetic marker next to a first-order gradiometer. Measuring this variation at various points was possible to generate planar images that recently came to be produced in systems with multiple detectors, said multi-channels. From planar images, also producing tomographic images of simulators BAC bars in a system of 13 channels using only the center channel, with good results when applied to simple objects as one and two bars. When testing the resolution of the system with more elaborate forms the quality and resolution of images reconstructed is not satisfactory, which would be solved by increasing the spatial sampling rate and hence the acquisition time. The present system works with an acquisition time of about five hours. Whereas this system will be applied for in vivo experiments, the acquisition time became a ...

A Biosusceptometria de corrente alternada (BAC) é uma ferramenta de pesquisa que vem sendo bastante explorada pelo grupo de Biomagnetismo IBB-UNESP para monitoramento do trato gastrointestinal, sua resposta a uma droga conhecida ou desempenho in vivo de formas farmacêuticas sólidas. Nesse período a BAC, que possui as características de alta sensibilidade e baixo custo, foi desenvolvida primariamente para registrar sinais de atividade de contração e trânsito do trato gastrintestinal humano. Com a possibilidade de se produzir imagens com esta instrumentação, foi possível avaliar diferentes situações in vitro e in vivo para estudos fisiológicos e farmacêuticos. Considerando o bom desempenho deste sistema para produzir imagens planares, o primeiro objetivo com o sistema tomografia por BAC (tBAC) foi avaliar o desempenho do sistema de BAC para produzir imagens tomográficas de fantomas ferromagnéticos para um sistema monocanal. Todas essas aplicações só foram possíveis por causa de sua sensibilidade a materiais de alta suscepitibilidade magnética, como ferrita, que permitem produzir um sinal elétrico proporcional à variação do fluxo magnético gerada pela presença do marcador magnético próximo a um gradiômetro de primeira ordem. Medindo esta variação em diversos pontos foi possível gerar imagens planares que, recentemente, passaram a ser produzidas com sistemas com vários detectores, ditos multi-canais. A partir das imagens planares, produzindo também imagens tomográficas de simuladores de barras em um sistema BAC de 13 canais utilizando apenas o canal central, com bons resultados quando empregado para objetos simples como uma e duas barras. Ao testar a resolução do sistema com formas mais elaboradas a qualidade e a resolução das imagens reconstruída não foi satisfatória, o que seria resolvido aumentando a taxa de amostragem espacial e, consequentemente o tempo de aquisição de aproximadamente de cinco ...
Keywords: Tomografia; Indução magnetica; Biotecnologia; Biossensores; Biomagnetismo; Pesquisa qualitativa; Radiografia - Qualidade da imagem; Tomography